Sulforaphane Ameliorates the Severity of Psoriasis and SLE by Modulating Effector Cells and Reducing Oxidative Stress - Du, Pei; Zhang, Wenqian; Cui, Haobo; He, Wei; Lu, Shuang; Jia, Sujie; Zhao, Ming (Frontiers in Pharmacology, 2022)
Background: Sulforaphane, which is found in cruciferous vegetables, has been reported to exhibit anti-inflammatory, antioxidant, and antitumour activities. However, whether sulforaphane has therapeutic effects on inflammatory or autoimmune skin diseases, including psoriasis and systemic lupus erythematosus (SLE), is unclear. Methods: The therapeutic effects of sulforaphane were analysed in Imiquimod (IMQ)-induced psoriasis-like mice and lupus-prone MRL/lpr mice. In IMQ-induced psoriasis-like mice treated with sulforaphane (10, 20 mg/kg) or vehicle control, pathological phenotypes were assessed by the PASI score, haematoxylin-eosin staining (H&E) and quantifying of acanthosis and dermal inflammatory cell infiltration and the proportions of Th subtypes in draining lymph nodes (dLNs) and spleens were examined by flow cytometry. In MRL/lpr mice treated with sulforaphane (15 mg/kg) or vehicle control, mortality and fluctuations in proteinuria were observed, and the glomerular pathology was examined by H&E staining. C3 and IgG deposition in kidney sections was examined by immunofluorescence staining. The proportions of plasma cells, Tfh cells, neutrophils and dendritic cells in the dLNs and spleens were examined by flow cytometry. Finally, we examined the Malondialdehyde (MDA) concentration and expression of Prdx1, Nqo1, Hmox1, and Gss by thiobarbituric acid reactive substance assay and reverse transcription-quantitative polymerase chain reaction (RT-qPCR). Results: Sulforaphane ameliorated skin lesions in an IMQ-induced psoriasis-like mouse model and renal damage in lupus-prone MRL/lpr mice. In IMQ-induced psoriasis-like mice, sulforaphane reduced the proportions of Th1 and Th17 cells and increased the expression of antioxidant gene Prdx1. Furthermore, our results demonstrated that sulforaphane increased the lifespan and reduced renal damage in lupus-prone MRL/lpr mice, decreased the proportions of plasma cells, Tfh cells, neutrophils, and dendritic cells and reduced the concentration of MDA and increased the expression of Prdx1. Conclusion: Sulforaphane has significant therapeutic effects on IMQ-induced psoriasis-like mice and lupus-like MRL/Lpr mice by reducing inflammatory and autoimmune-related cells and oxidative stress. These findings provide new evidence for developing natural products to treat inflammatory and autoimmune diseases.